2020
DOI: 10.1111/jcmm.15943
|View full text |Cite
|
Sign up to set email alerts
|

circ_SEPT9, a newly identified circular RNA, promotes oral squamous cell carcinoma progression through miR‐1225/PKN2 axis

Abstract: Circular RNAs (circRNAs) represent a newly discovered class of endogenous non‐coding RNAs which are widely expressed and play important roles in disease progression. However, the function of circRNAs in oral squamous cell carcinoma (OSCC) still remains largely unknown. In this research, we found that circ_SEPT9 was highly expressed in OSCC cell lines and tumour tissues. Results showed that circ_SEPT9 promoted OSCC proliferation and tumour growth. And, circ_SEPT9 also enhanced the migration and invasion of OSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Moreover, a recent study showed an increase in circ_0005320 in OSCC, and elevation of circ_0005320 accelerated OSCC cell survival, invasion, and migration by miR-1225/Protein Kinase N2 axis. However, large-scale identifications of circ_0005320 in the tumorigenesis of OSCC are not yet reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study showed an increase in circ_0005320 in OSCC, and elevation of circ_0005320 accelerated OSCC cell survival, invasion, and migration by miR-1225/Protein Kinase N2 axis. However, large-scale identifications of circ_0005320 in the tumorigenesis of OSCC are not yet reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…LB of body fluids is commonly used for the diagnosis of multiple human diseases [36,37]. Although miRNAs have been widely assessed as biomarkers in body fluids [38,39], it was recently reported that circRNAs are highly resistant to RNA degradation by exonucleases compared with miRNAs [4,9,10]. CircRNAs are also widely distributed not only within cells but in the extracellular space and various body fluids [26,40].…”
Section: Discussionmentioning
confidence: 99%
“…Jeck et al reported that putative functions of circRNA are not only miRNA sponge but also regulation of transcription, interactions with RNA binding proteins, and translation of circRNAs [8]. Among them, circRNAs have multiple microRNA (miRNA) binding sites, and circRNA binding leads to regulation of the expression of those miRNAs and their target genes by acting as a competing endogenous RNA [4,9,10]. However, the underlying molecular mechanisms and clinical correlation between circRNAs and tumor progression are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…e existent study of the function of PKN2 in tumor is relatively controversial. Particularly, PKN2 was reported as an oncogene in oral squamous cell carcinoma progression [44]. On the contrary, PKN2 was identified to inhibit tumor-associated macrophages (TAMs) polarization and tumor growth in colon cancer [45].…”
Section: Discussionmentioning
confidence: 99%